Decreased Prefrontal Cortical Dopamine Transmission in Alcoholism - Narendran, Rajesh; Mason, Neale Scott; Paris, Jennifer; Himes, Michael L; Douaihy, Antoine B; Frankle, W. Gordon (American Journal of Psychiatry, 2014)
ObjectiveBasic studies have demonstrated that optimal levels of prefrontal cortical dopamine are critical to various executive functions such as working memory, attention, inhibitory control, and risk/reward decisions, all of which are impaired in addictive disorders such as alcoholism. Based on this and imaging studies of alcoholism that have demonstrated less dopamine in the striatum, the authors hypothesized decreased dopamine transmission in the prefrontal cortex in persons with alcohol dependence.MethodTo test this hypothesis, amphetamine and [11C]FLB 457 positron emission tomography were used to measure cortical dopamine transmission in 21 recently abstinent persons with alcohol dependence and 21 matched healthy comparison subjects. [11C]FLB 457 binding potential, specific compared to nondisplaceable uptake (BPND), was measured in subjects with kinetic analysis using the arterial input function both before and after 0.5 mg kg−1 of d-amphetamine.ResultsAmphetamine-induced displacement of [11C]FLB 457 binding potential (ΔBPND) was significantly smaller in the cortical regions in the alcohol-dependent group compared with the healthy comparison group. Cortical regions that demonstrated lower dopamine transmission in the alcohol-dependent group included the dorsolateral prefrontal cortex, medial prefrontal cortex, orbital frontal cortex, temporal cortex, and medial temporal lobe.ConclusionsThe results of this study, for the first time, unambiguously demonstrate decreased dopamine transmission in the cortex in alcoholism. Further research is necessary to understand the clinical relevance of decreased cortical dopamine as to whether it is related to impaired executive function, relapse, and outcome in alcoholism.